UPAYA PENINGKATAN PRESTASI BELAJAR SISWA MATA PELAJARAN EKONOMI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TSTS (TWO STAY TWO STRAY) PADA SISWA KELAS X A SMA PGRI 1 MAOSPATI MAGETAN TAHUN PELAJARAN 2012/2013 - Sudarmiani Sudarmiani (Universitas PGRI Madiun, 2013)
Based on initial observations and interviews with high school Economics teacher PGRI 1 Maospati Magetan note that the average value of the cognitive aspects of students in the class XA is 62. These results indicate that the numbers are still low com- pared to other classes. The learning process is commonly carried out using a model of discourse as a whole, namely the delivery of content to students and interspersed ques- tions and answers. This leads to learning as students tend to be passive and less meaning- fullearning for students. Students gain experience less direct, and less teacher provides opportunities as well as self- confidence in the students to be active in learning. It also adversely affects the affective aspects of students. Based on these problems researchers to make improvements by implementing cooperative learning model of two stay two stray ( TSTS ). The learning model involves students actively in learning activities. Pakok mind model of cooperative learning are two stay two stray provide an opportunity for groups to share results and information to other groups. The approach used in this study is a qualitative approach to classroom action research that consists of 2 cycles. Research subject is class XA SMA PGRI 1 Maospati Magetan , the number of 32 stu- dents. Data collection methods used in this study is a test of the cognitive aspects of economic subjects in the form of daily tests at the end of the cycle, and affective aspects of the observation sheets during the learning process. The results of observations of stu- dents' learning in classroom situations XA SMA PGRI 1 Maospati Magetan increased, namely: ( 1 ) The interest and attention of students in the learning process from 67.25% to 84.60% increased 17.35% ( 2 ) The active participation of students in asking from 54.10% to 68.25% an increase of 14.15% ( 3 ) the active participation of students in answering / expression from 52.22% to 69.45% increased 17.23% ( 4 ) the level of stu- dent discipline in the process of learning from 60.500/0 to 78.13% 17.63% an increase. The results of observations III group activities has increased, namely: ( 1 ) The active participation of students in an opinion from 51.58% to 68.75% increased 17.17% (2) The active participation of students in asking from 50.60% to 66.68% increased 16.08% (3)the active participation of students in answering questions from 53.12% to 71.88% increased18.76% (4) Respect tile opinion of friends from 55.50% to 74.850/0 increased 19,35% (5) Cooperation in completing a task group from 60.35% to 78.25% 17.90% an increase. Another thing shown by the increased learning outcomes from 65.63 % to 84.38%. Thus there is an increase of 18.75% .While the average value of learning outcomes in the first cycle is 71 increased to 82 in the second cycle. Learning model two stay two stray ( TSTS ) can improve cognitive and affective aspects of students by providing a learning environment that is fun discussions, opportunities for students to learn actively exchange information with peers and materials, conveying the idea to friends, submit answers and questions discussion of the problem, and it requires cooperation within the group.